2015
DOI: 10.1093/aob/mcv113
|View full text |Cite
|
Sign up to set email alerts
|

Plant defence as a complex and changing phenotype throughout ontogeny

Abstract: Background and Aims Ontogenetic changes in anti-herbivore defences are common and result from variation in resource availability and herbivore damage throughout plant development. However, little is known about the simultaneous changes of multiple defences across the entire development of plants, and how such changes affect plant damage in the field. The aim of this study was to assess if changes in the major types of plant resistance and tolerance can explain natural herbivore damage throughout plant ontogeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 52 publications
3
62
0
Order By: Relevance
“…; Barton ; Ochoa‐Lopez et al . ). If ontogenetic trajectories in plant defence are indeed adaptive, the regulatory mechanisms behind their expression are likely to be important targets of selection.…”
Section: Regulatory Mechanisms Underlying Ontogenetic Trajectories Inmentioning
confidence: 97%
See 3 more Smart Citations
“…; Barton ; Ochoa‐Lopez et al . ). If ontogenetic trajectories in plant defence are indeed adaptive, the regulatory mechanisms behind their expression are likely to be important targets of selection.…”
Section: Regulatory Mechanisms Underlying Ontogenetic Trajectories Inmentioning
confidence: 97%
“…Similarly, myrmecophytic plants often have greater reward production in extrafloral nectaries of leaves close to reproductive structures, suggesting a more intense selective pressure of herbivores during the reproductive stage (Ochoa‐Lopez et al . ), although this remains to be formally tested. Overall, there is a lack of data on stage‐specific herbivore selection pressures, and this represents a fair challenge for our understanding of the evolution of defence ontogenetic trajectories.…”
Section: Drivers Of Ontogenetic Changes In Plant Defencementioning
confidence: 99%
See 2 more Smart Citations
“…Ontogenetic changes in laminar area:perimeter ratio, specific leaf area, percent of parenchyma and stomatal length and density have been also reported in different habitats, as is the case for Lasthenia species associated with terrestrial or vernal pool habitats (Forrestel et al., ). Because the expression of multiple plant defences can also vary throughout plant ontogeny (see Barton, ; Ochoa‐López, Villamil, Zedillo‐Avelleyra, & Boege, ; Quintero, Lampert, & Bowers, ), changes in trade‐offs and correlations between leaf economic and defensive traits during plant development are expected (Arntz & Delph, ). For example, Mason and Donovan () demonstrated that ontogenetic changes in leaf economic traits are conditioned by resource trade‐offs with plant defence in three species of Helianthus .…”
Section: Introductionmentioning
confidence: 99%